Hypoglycemia Associated With Drug–Drug Interactions in Patients With Type 2 Diabetes Mellitus Using Dipeptidylpeptidase-4 Inhibitors - Ray, Chin-Ying; Wu, Victor Chien-Chia; Wang, Chun-Li; Tu, Hui-Tzu; Huang, Yu-Tung; Kuo, Chang-Fu; Chang, Shang-Hung (Frontiers in Pharmacology, 2021)
Background: Dipeptidylpeptidase-4 inhibitors (DPP-4i’s) are considered to be safe for patients with type 2 diabetes mellitus (T2DM). However, little is known about drug–drug interactions between DPP-4i’s and concurrent medications. Methods: Data on patients using DPP-4i’s for T2DM during 2011–2017 were retrieved from Chang Gung Research Database provided by Chang Gung Memorial Hospital. Patients were excluded if they were aged <30 years or >90 years; had incomplete demographic data; had insulinoma; or had records of concomitant insulin use. A generalized estimating equation–based Poisson model was employed for statistical analysis. The primary outcome was hypoglycemia events. Results: We retrieved data on a total of 97,227 patients using DPP-4i’s. After patients were excluded according to the mentioned criteria, the remaining 77,047 DPP-4i users were studied (mean age 64 ± 12 years, men 54.4%). The most common medications coprescribed with DPP4is over all person-quarters were acetaminophen, simvastatin, fluvastatin, and colchicine (all >20,000 person-quarters). The combinations of a DPP-4i with bumetanide, captopril, colchicine, acetaminophen, cotrimoxazole, and pantoprazole were associated with an increased risk of hypoglycemia. Compared with the ratios observed for person-quarters of DPP-4i use alone (reference category), the adjusted prevalence ratios per 100 person-years of hypoglycemia for person-quarters of DPP-4i use in combination with bumetanide, captopril, colchicine, acetaminophen, cotrimoxazole, and pantoprazole were 2.44 (95% confidence interval [CI], 1.78–3.36), 2.97 (95% CI, 2.26–3.90), 1.87 (95% CI, 1.44–2.42), 2.83 (95% CI, 2.44–3.29), 2.27 (95% CI, 1.27–4.04), and 3.03 (95% CI, 1.96–4.68), respectively. On the other hand, there was no increased hypoglycemia for DPP-4i use in combination with fosinopril, verapamil, simvastatin, fluvastatin, gemfibrozil, duloxetine, and sulfinpyrazone. Conclusions: Among patients taking DPP-4i’s for T2DM, concurrent use of such inhibitors with bumetanide, captopril, acetaminophen, and pantoprazole was associated with an increased risk of hypoglycemia compared with the use of DPP-4i’s alone. Physicians prescribing DPP-4i’s should consider the potential risks associated with their concomitant use with other drugs.